Differential Effects of Long-Term Caloric Restriction and Dietary Protein Source on Bone and Marrow Fat of the Aging Rat. (16th April 2020) - Duque, Gustavo; Al Saedi, Ahmed; Rivas, Daniel; Miard, Stéphanie; Ferland, Guylaine; Picard, Frederic; Gaudreau, Pierrette
Abstract: Long-term caloric restriction (CR) has been shown to be beneficial to various tissues and organs. In contrast, CR exerts differential effects on bone, which could be due in part to the nature of the protein regime utilized. Male Sprague Dawley rats (8-month-old) were subjected for 12 months to 40% CR in macronutrients and compared with rats fed ad libitum for the same period. Casein- and soy-fed groups were compared. There was a significant decrease in bone quality in both CR groups, which was independent of the source of protein in the diet. In contrast, the group fed soy protein ad libitum showed better bone quality and higher levels of bone formation compared with casein-fed animals. Notably, bone marrow adipocytes were not mobilized upon CR as demonstrated by an absence of change in adipocyte number and tissue expression of leptin. This study demonstrates that the negative effect of CR on bone quality could not be prevented by the most common protein regimes.